Forecast Evaluation. - Demski, Joel S.; Feltham, Gerald A. (The Accounting Review, 1972)
The article discusses forecast evaluation in accounting. Accounting data are often used in the development of forecasts and accountants are often called on to make forecasts. Development of a variable overhead rate per direct labor hour may, for example, be viewed as development of a forecast–whether it is used in a standard cost system, in a budget, or in a product mix decision. Similarly, establishment of a depreciation policy requires a forecast of service life. Furthermore, the ability to forecast some specific outcome has been offered as a criterion for selection among accounting alternatives. But, whatever its ultimate purpose, development of a forecast constitutes a decision–a conscious choice among alternatives. The concern in this paper is limited to this decision aspect of forecasting. In particular, in the first section it is demonstrated that selection among forecast alternatives is a subset of the accountant's general problem of selection among information alternatives. Following this, characterization is done of prevailing methods of selecting among forecast alternatives as a simplification of the basic information choice problem. The paper then concludes with two illustrative simulations.